Effectivity of Intra-Arab Trade of Natural Resources in Achieving Development - Alfalasi, Mohammad (The Arab Journal of Administration, 2020)
Arab States had many opportunities and efforts to improve cooperation through agreements, treaties, and decisions made in different fields of intra-Arab trade, in order to connect in a common market later. Internal and external conditions had a crucial effect in creating and activating agreements on areas of development –especially in the least developed Arab countries-, in economic, social, cultural, and environmental aspects; hence, achieving development within economic integration in trade. Therefore, Arab states were keen to sign agreements and commitments based on bilateral and multilateral agreements with non-Arab states, while development could have been much better for their interest, if better solutions were founded to resolve conflicts in internal conditions and instability, and contract and diversions in goals which had to be mutually inclusive, and in need for cooperation and common action in seeking development within certain strategic visions and goals.